When troglomorphism dupes taxonomists: morphology and molecules reveal the first pyramidopid harvestman (Arachnida, Opiliones, Pyramidopidae) from the New World - Cruz López, Jesús A. (2016)
Cavernicolous species that exhibit a high degree of troglomorphism often provide some of the most intriguing evolutionary riddles. For such taxa, the correct systematic arrangement is difficult to determine and becomes problematic when based solely on highly convergent external morphological characters, leading to exaggerated support of spurious relationships. For the arachnid order Opiliones, examination of male genitalia morphology often aids in determining the family to which a particular taxon belongs. However, many taxa described prior to the 1990s lack detailed descriptions or drawings of this important character and, for highly-derived species, it is may still be necessary to seek support from additional sources of characters (e.g. molecular data) to accurately assess systematic placement. The enigmatic species Stygnomma pecki Goodnight & Goodnight, from a cave in Belize proved to be especially difficult to place based on morphological characters alone. Thus, using a previously published dataset for laniatorean harvestmen, we carried out a robust phylogenetic analysis aiming to determine the evolutionary relationship of this Neotropical troglomophic species. Informed by the results of the molecular phylogenetic analysis of 88 terminals representing Laniatores, we describe Jarmilana gen. nov. and provide a redescription of the type species Jarmilana pecki (Goodnight & Goodnight,) comb. nov. Morphological evidence, including male genitalia morphology, supports the inclusion of J. pecki in the family Pyramidopidae. This represents the first record for the family Pyramidopidae in the New World, raising the question of whether this represents transoceanic dispersal or a relict of an ancient widespread tropical Gondwanan distribution.